Prospecção de compostos químicos terapêuticos com potencial inibitório do exoproteoma de Acanthamoeba spp - Marujo, Fabio Iglesias [UNIFESP] (2016)
Introduction: Acanthamoeba keratitis has presented an increased incidence and ocular morbidity indexes. During pathogenesis, corneal invasion of the amoeba is obtained by the secretion of an exoproteome, which include enzymes believed to be its main virulence factors. Treatment should be started as soon as possible and last for a long period, but the specific therapeutic regimen still lacks a consensus. The use of low doses of antiamoebic medications as proteolysis inhibitors may be a new and promising form of treatment, in which the focus is stopping the pathological process, rather than just attacking the microorganism itself. Materials and Methods: A sterile 96 well assay black plate was used to dilute one antiamoebic drug, exoproteome, EnzChek® Gelatinase/Collagenase Assay Kit substrate and reaction buffer in each well. Four different concentrations of each drug (Polyhexamethylene biguanide, Chlorhexidine gluconate, Hexamidine di-isethionate and Propamidine Isethionate) were tested in exoproteome from four different strains of Acanthamoeba. A second assay consisted in evaluating toxicity in commercially available certified standard cell lines of corneal keratocytes (SIRC) exposed to different dosages of PHMB, chlorhexidine, hexamidine and propamidine in the presence and absence of exoproteom. For this, PrestoBlue® Cell Viability Reagent was used. All assays used saline solution (NaCl 0.9%) as solvent and were conducted in triplicate. Fluorescence readings were performed by SpectraMax® Paradigm® Multi-Mode Detection Platform. Results: All compounds reduced proteolysis and there was a clear correlation between the concentration of the drug and its inhibitory effect, which was more pronounced in higher concentrations of hexamidine, propamidine and chlorhexidine. However the opposite occurred with PHMB, with concentrations as low as 0.0025% having a powerful inhibitory effect compared to the null effect of 0.02%. Regarding the SIRC keratocytes assay all drugs tested caused a decrease in cell viability, which was directly proportional to its concentration, both in the presence or absence of exoproteome. Discussion and conclusion: The formation of micelles of PHMB may be responsible for the decrease in its inhibitory effect in high concentrations. Therefore, a high concentration of antiamoebic drugs does not necessarily improve the clinical outcome, not only by the increase of citotoxicity, but also by lowering the inhibitory effect it would have on proteolisis. Studies using low-concentration PHMB in Acanthamoeba keratitis should be conducted to establish the most effective dosage in those cases.